Perioperative Management and Clinical Outcomes of Liver Transplantation for Children with Homozygous Familial Hypercholesterolemia - Huan-Rong Qiu; Liang Zhang; Zhi-Jun Zhu (Medicina, 2022)
Background and Objectives: Liver transplantation (LT) has been accepted as a life-saving option as a last resort for children with homozygous familial hypercholesterolemia (HoFH). Perioperative management of LT for HoFH poses extra challenges for clinicians largely due to premature atherosclerotic cardiovascular diseases (ASCVDs). We aimed to analyze our data of pediatric LT recipients with HoFH, with special attention paid to perioperative management and clinical outcomes. Materials and Methods: After obtaining approval from the local ethics committee, the clinical data of pediatric patients with HoFH who underwent LT at our institution between January 2014 and February 2021 were retrospectively studied. Results: Six pediatric LT recipients with HoFH were included in the analysis. Although ASCVDs were common before LT, all children with HoFH survived the perioperative period without in-hospital mortality. However, one patient experienced acute myocardial infarction two months following LT and was successfully treated with medical interventions. Post-LT metabolic improvement was shown by declines in serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels in the early post-LT period (for TC: 14.7 ± 3.2 mmol/L vs. 5.5 ± 1.8 mmol/L, p < 0.001; for LDL-C: 10.6 ± 2.2 mmol/L vs. 3.6 ± 1.2 mmol/L, p < 0.001, respectively) and at the last follow-up (for TC: 14.7 ± 3.2 mmol/L vs. 4.5 ± 0.9 mmol/L, p = 0.001; for LDL-C: 10.6 ± 2.2 mmol/L vs. 2.8 ± 0.6 mmol/L, p = 0.001, respectively). Dietary restrictions could be lifted after LT. However, three patients required restarting lipid-lowering therapy after LT due to suboptimal LDL-C levels and progression of ASCVDs. Conclusions: Our data suggest that LT can be a safe and feasible therapeutic option for well-selected patients with HoFH, offering relaxed dietary restrictions and remarkable reductions in LDL-C levels. However, concerns remain regarding progression of ASCVDs after LT.